P-128 All about me: the patient as a person in palliative care. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Austen, Emma; Wheatland, Sarah; Timms, Sue; Partridge, Michael
Abstract : Background: Patients with serious illness are at a risk of de-personalised, over-medicalised care as they move into later life (Shippee, Shippee, Mobley et al ., 2018). Research shows the importance of the expression of feelings and being seen as an individual during the advanced stages of illness (Kennedy, 2016; Sampson, Finlay, Byrne et al ., 2014). Aim: To evaluate our 'This is Me' white-boards from patient, relatives' and staff perspectives to identify their contribution to a person-centred approach in the hospice. Methods: Boards in patients' rooms were re-branded 'This is Me' boards. Patients and relatives were encouraged to write and draw on them, creating an expression of them as a person. Questionnaire feedback was analysed and themes identified (May-June 2018). Results: Patients and relatives: Patients felt it helped staff view them more as a person Provided a motivational function and a timetable Made the environment more personal and homely. Staff: Informality and freedom of expression to project a new perspective The creativity deployed was uplifting Highlighted the uniqueness of each patient Power of visual imagery to inform care. Conclusion: Evaluation of the 'This is Me' boards demonstrates a dynamic approach to patient-centred care where individual wishes and goals are communicated to all staff, and relatives in a meaningful patient-led approach.